밀 영농부산물 소각에 따른 온실가스 배출계수 개발 - 송새눈(Song, Saenun); 우지윤(Woo, Jiyun); 김민욱(Kim, Minwook); 김승진(Kim, Seungjin); 노준영(Roh, JoonYoung); 전의찬(Jeon, Eui-Chan) (한국기후변화학회지, 2024)
As of 2019, the greenhouse gas emissions from agricultural byproduct incineration amounted to 15.83 thousand tons CO2eq. Only CH4 and N2O emissions are reported from agricultural byproduct incineration, with CO2 not being considered carbon neutral. The emission coefficients used to estimate greenhouse gases in this sector rely on the 1996 IPCC GL (Guidelines for National Greenhouse Gas Inventories) values and incorporate oxidation rates and nitrogen content for specific crops. However, there is a need for improvement as emission coefficients are applied without considering crop-specific characteristics. This study focuses on wheat as the target crop, with samples collected during the harvest season in June. To simulate real open burning sites, experiments were conducted using an experimental chamber constructed based on EPA method 5G (Determination of particulate matter emissions from wood heaters - dilution tunnel sampling location) and EPA-600/R-96-128 (Evaluation of Emission from the Open Burning Of Land-Clearing Debris). Sample gases were collected in Tedlar bags using a lung sampler (EPA Method 18) and analyzed via GC-FID to determine the concentrations of CH4 and N2O. The emission coefficients developed in this study for wheat agricultural byproduct incineration can serve as foundational data for estimating greenhouse gas emissions in the agricultural sector, enhancing the reliability of national inventories. KCI Citation Count: 0